Test and evaluation method for scribing adhesive force of hydraulic support water paint

Through the hydraulic support water-based paint scratch adhesion test and quantitative evaluation method, the subjectivity and uncertainty of traditional coating adhesion test are solved, the accuracy and comparability of coating adhesion test are achieved, and the hydraulic support is improved Quality control of surface coatings.

CN119178721APending Publication Date: 2024-12-24CHINACOAL BEIJING COAL MINING MACHINERY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411299095.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Traditional coating adhesion testing methods are subjective and uncertain, unable to provide reliable quantitative evaluation, and it is difficult to achieve objective comparison and quality control of coating performance.

Method used

The adhesion test method of hydraulic support water-based paint scratches is used. By spraying a coating of standard thickness, the scratch test and salt spray moisture and heat test are carried out to measure the width after scratch spread and peeling. Combined with quantitative evaluation methods, adhesion scores are provided to ensure that Accuracy and comparability of test results.

Benefits of technology

It improves the objectivity and reliability of coating adhesion test, provides scientific evaluation basis, enhances the quality control level of hydraulic support surface coating, and ensures the repeatability and comparability of test results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119178721A_ABST
    Figure CN119178721A_ABST
Patent Text Reader

Abstract

The invention relates to a method for testing and evaluating water paint gridding adhesive force of a hydraulic support. The test method comprises the following test steps: S1, preparing a sample and spraying a water-based paint coating to ensure that the thickness of the coating is between 25 microns and 150 microns; s2, a 1 mm or 2 mm scratching knife is used for scratching grids on the coating, and it is ensured that scratches penetrate through the coating to reach the base material; s3, putting the sample into a test box, and alternately carrying out salt mist and damp heat tests; and S4, observing and recording the width of the coating after the scratches spread and the width of the coating after the scratches are stripped in the gridding area. According to the method, a quantitative evaluation method is adopted to replace a traditional mode depending on visual observation and experience judgment, so that the objectivity and reliability of a test result are remarkably improved. The method not only ensures the consistency and repeatability of the test process, but also realizes quantitative evaluation of the adhesive force of the coating by defining an adhesive force score, a series of parameters and weights thereof, and provides clear data support for the improvement of the performance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water-based paint, and in particular to a test and evaluation method for the cross-cutting adhesion of water-based paint for a hydraulic support. Background Art

[0002] In the field of modern industrial manufacturing, especially in industries such as mining and oil drilling, hydraulic supports, as a key equipment, must be able to work stably and for a long time in extremely harsh environments. Hydraulic supports not only bear huge mechanical loads, but also face various environmental challenges such as salt spray corrosion and wet heat erosion. In order to meet these challenges, ensuring the quality of the surface coating of hydraulic supports has become a crucial issue. The coating must not only have excellent anti-corrosion properties, but also have sufficient adhesion to resist the influence of various external environmental factors.

[0003] Traditional coating adhesion test methods usually rely on intuitive visual inspection and empirical judgment, such as evaluating the adhesion of coatings through simple line or circle tests. However, this method has obvious shortcomings: on the one hand, the test results are often highly subjective, and different operators will come to different conclusions; on the other hand, due to the lack of a unified quantitative standard, it is difficult to achieve objective comparison and evaluation of coating performance. In addition, traditional methods can usually only qualitatively describe the performance of the coating and cannot provide a repeatable and quantifiable evaluation basis, which is a significant defect for quality control in industrial production. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a test and evaluation method for the cross-cut adhesion of water-based paint on a hydraulic support, which solves the subjectivity and uncertainty problems existing in traditional coating adhesion test methods and provides more accurate and reliable test results through quantitative evaluation.

[0006] (II) Technical solution

[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0008] In a first aspect, an embodiment of the present invention provides a test of the cross-cut adhesion of water-based paint for a hydraulic support, comprising the following steps:

[0009] S1. Prepare the sample and spray the coating:

[0010] Select the substrate and ensure that the surface is clean and free of impurities;

[0011] Spray water-based paint to ensure that the coating thickness is between 25μm and 150μm;

[0012] S2. Perform a cross-cut test:

[0013] Use a 1mm or 2mm scratcher to draw a grid on the coating, make sure the scratches penetrate the coating to the substrate, and measure the width of the scratches;

[0014] S3. Conduct salt spray and damp heat tests:

[0015] Place the sample that has completed the cross-cut test in the test chamber and conduct salt spray and damp heat tests alternately. Each test is carried out according to the scheduled time.

[0016] S4. Test the width of the scratch after it spreads and the width of the scratch after it peels off in the cross-cut area:

[0017] After taking the specimen out of the test chamber, observe and record the width of the scratch after propagation and the width of the scratch after peeling in the cross-cut area.

[0018] The present invention provides a cross-cut adhesion test method for a hydraulic support water-based paint, which has multiple significant beneficial effects. First, by strictly controlling the coating thickness between 25 μm and 150 μm, it is ensured that the preparation of the sample meets the standard, thereby improving the reliability and consistency of the test results. Secondly, when performing the cross-cut test, a 1 mm or 2 mm scratching knife is used to draw a grid, and it is ensured that the scratches penetrate the coating to reach the substrate, so that the consistency of the test conditions can be ensured and the results can be avoided from being affected by different scratch depths. In addition, by alternately performing salt spray and wet heat tests, the extreme environmental conditions encountered by the hydraulic support in actual use are simulated, so that the performance of the coating in harsh environments can be more realistically evaluated. By measuring and recording the width of the scratch after propagation and the width of the scratch after peeling in the cross-cut area, specific quantitative data can be obtained, which is helpful to more accurately evaluate the adhesion of the coating. Finally, since each step has clear operating instructions, the test conditions of different batches of samples are consistent, and the comparability of the test results is enhanced. In summary, this test method effectively improves the accuracy and reliability of the test results through a series of standardized steps and strict condition control, and provides a scientific basis for the performance evaluation of water-based paint coatings on hydraulic supports.

[0019] Optionally, the water-based paint is water-based polyurethane paint.

[0020] Optionally, in step S1, after spraying the water-based paint, the coating is allowed to dry naturally or is baked and cured to ensure that the coating is completely cured, with a baking temperature of 80° C. to 100° C. and a baking time of 30 minutes to 1 hour.

[0021] Natural drying or baking curing can ensure that the coating is fully cured, thereby improving the hardness and adhesion of the coating, so that it can show better performance in subsequent cross-cut tests and environmental tests. Secondly, the method and conditions for coating curing are clearly specified. Whether it is natural drying or baking curing, the consistency of test conditions is ensured, and the repeatability and reliability of test results are improved. In addition, the baking curing method can complete the curing process of the coating in a shorter time. Compared with natural drying, it greatly shortens the preparation time for the test and improves work efficiency. Baking curing also helps to promote the optimization of the internal structure of the coating, making the coating more uniform and dense, and enhancing the corrosion resistance and environmental erosion resistance of the coating.

[0022] Optionally, in step S3, the duration of each salt spray test and damp heat test is 2 hours, and the two tests are performed alternately until the cumulative time of the salt spray test and the cumulative time of the damp heat test each reach at least 200 hours.

[0023] Optionally, in steps S2 and S4, in each cross-cut area, the length of the scratch is equally divided into several sections, and the scratch width, the scratch width after propagation, and the scratch width after peeling of each section are measured respectively.

[0024] First, by dividing the scratch length into several segments and measuring them separately, more detailed data can be obtained, thereby improving the accuracy of the measurement results. This method can more accurately reflect the changes in the adhesion of the coating at different positions and enhance the reliability of the results. Secondly, the data of the subdivided measurement can be better used for statistical analysis, help identify the distribution characteristics of coating performance, and provide a scientific basis for subsequent quality improvement. In addition, by subdividing the measurement, richer data can be obtained, providing more dimensional information for the evaluation of coating adhesion, which helps to formulate more detailed and comprehensive evaluation standards. Furthermore, this method ensures the consistency of the test operation, improves the repeatability of the test results, and facilitates the comparison and verification of results between different laboratories. Finally, the subdivided measurement method makes the test process more standardized, reduces the arbitrariness of the operation, and improves the overall efficiency and standardization of the test. In summary, by dividing the scratch length into several segments in steps S2 and S4 and measuring the relevant width of each segment respectively, not only the measurement accuracy and the reliability of the results are improved, but also more detailed and comprehensive data support is provided for the evaluation of coating adhesion, thereby improving the scientificity and practicality of the test method.

[0025] In a second aspect, an embodiment of the present invention provides an evaluation method for a test of the cross-cut adhesion of a water-based paint for a hydraulic support, characterized in that the evaluation method is used to evaluate the cross-cut adhesion score of the water-based paint for the hydraulic support, and the calculated adhesion score A represents the magnitude of the cross-cut adhesion, thereby achieving a quantitative evaluation of the coating adhesion;

[0026]

[0027] In the formula, A j represents the adhesion score of the jth test point, A represents the average adhesion score of all test points; P i,j represents the measured value of the i-th parameter at the j-th detection point, P i,max represents the upper limit of the i-th parameter range, P i,min represents the lower limit of the i-th parameter range, n represents the number of measurement points, and w i Represents the weight of the i-th parameter.

[0028] Evaluation score (A j ) is closer to 1, indicating that the coating has better adhesion performance in the current environment. This is because the evaluation score (A j ) is obtained by adding the weighted scores of all parameters and dividing by the number of parameters, so when all parameters are close to their maximum values, the weighted scores will be higher, resulting in an evaluation score (A j ) is close to 1.

[0029] First, by calculating the adhesion score A, the adhesion evaluation is converted into a quantitative evaluation, making the result more objective and accurate, and reducing the error of subjective judgment. Secondly, the evaluation method comprehensively considers multiple parameters (such as film thickness, temperature, salt spray concentration, humidity, etc.), and by defining the weight of each parameter, it systematically evaluates the adhesion of the coating and provides a comprehensive evaluation basis. In addition, by measuring multiple parameters at each test point and calculating the adhesion score A of each test point, the adhesion of each test point can be calculated. j , and then calculate the average adhesion score A of all test points. This method improves the accuracy of the evaluation and makes the result more reliable. i,max and P i,min ), making the results under different test conditions comparable, which helps to compare the results between different laboratories or different batches. i ), simplifies the complex relationship between multiple parameters, making the evaluation process more concise and clear, easy to understand and operate. Finally, by providing a comprehensive adhesion score, it provides strong data support for coating formula adjustment, production process optimization, etc., which helps to make more scientific and reasonable decisions.

[0030] In summary, the evaluation method provided in the embodiment of the present invention not only improves the objectivity and accuracy of the evaluation results by quantifying the adhesion score, but also provides a systematic, comparable and simplified solution for the comprehensive evaluation of coating adhesion, thereby improving the scientificity and practicality of the evaluation method.

[0031] Optionally, the evaluation method is to use a mechanical method to scratch the coating on the surface of the substrate to draw a plurality of quadrilaterals. i They represent film thickness B, temperature T, salt spray concentration C, humidity D, scratch width E, scratch width after propagation F and scratch width after peeling G respectively.

[0032] In order to comprehensively evaluate the adhesion of the water-based paint coating of the hydraulic support, the present invention not only considers external parameters such as film thickness, temperature, salt spray concentration, humidity, etc., but also adds mechanical performance parameters such as scratch width E, scratch width after propagation F, and scratch width after peeling G. This innovative combination brings many advantages:

[0033] First, static parameters such as film thickness, temperature, salt spray concentration and humidity reflect the stability of the coating under specific environmental conditions, such as mass changes and corrosion resistance during the curing process. However, relying solely on these static parameters cannot fully evaluate the mechanical damage faced by the coating during actual use. By adding the scratch width E, the width F after the scratch propagates, and the width G after the scratch peels off, the performance of the coating after mechanical damage can be more comprehensively evaluated. The scratch width E reflects the degree of damage to the coating at the time of initial damage, the width F after the scratch propagates shows the expansion of the coating after damage, and the width G after the scratch peels off directly reflects the strength of the adhesion between the coating and the substrate.

[0034] This combination not only makes up for the shortcomings of only considering static parameters, but also can evaluate the durability and reliability of the coating in practical applications from a dynamic perspective. Therefore, through this innovative combination, the present invention provides a more comprehensive and systematic coating adhesion evaluation method, which can better predict and evaluate the performance of the coating under complex environmental and mechanical stress conditions.

[0035] Scratch width E, scratch width F after propagation, and scratch width G after peeling are key indicators for evaluating the mechanical strength and adhesion of coatings. These parameters can directly reflect the performance of the coating when subjected to external forces, such as whether the coating is prone to cracking, peeling, or falling off. Through a comprehensive evaluation including scratch width E, scratch width F after propagation, and scratch width G after peeling, more references can be provided for the selection of coating materials, optimization of coating processes, and improvement of coating formulations, thereby continuously optimizing product design.

[0036] Film thickness directly affects the protective properties of the coating. Thicker coatings generally provide better protection, but in some cases also result in reduced flexibility and adhesion of the coating. Film thickness interacts with environmental factors such as temperature and humidity to affect the degree of curing and final adhesion of the coating. Film thickness needs to be considered in conjunction with parameters such as temperature and humidity to ensure that the coating is in optimal condition during the curing process. Appropriate film thickness can enhance the corrosion resistance of the coating.

[0037] The salt spray concentration reflects the corrosiveness of the environment. High salt spray concentration will accelerate the corrosion process of the coating and reduce the durability of the coating. The salt spray concentration, together with humidity, temperature and other parameters, simulates the corrosion resistance of the coating in the actual use environment. Humidity affects the curing process and corrosion resistance of the coating. High humidity causes the coating to absorb water and swell, affecting adhesion.

[0038] The scratch width reflects the initial damage degree of the coating when it is mechanically damaged. In dynamic testing, the scratch width, together with parameters such as film thickness and temperature, reflects the initial response of the coating under mechanical stress. The scratch propagation width reflects the expansion of the coating after mechanical damage. A smaller propagation width indicates that the coating has a better ability to resist crack propagation. The scratch propagation width, together with parameters such as scratch width and film thickness, reflects the long-term stability of the coating under mechanical stress.

[0039] The width of the scratch after peeling reflects the peeling of the coating after mechanical damage. A smaller peeling width indicates a stronger adhesion between the coating and the substrate. The width of the scratch after peeling, together with parameters such as film thickness and temperature, shows the adhesion performance of the coating under mechanical stress.

[0040] By combining static (film thickness, temperature, salt spray concentration, humidity) and dynamic (scratch width E, scratch propagation width F, scratch peeling width G) parameters, the performance of the coating under different environmental conditions can be comprehensively evaluated. Static parameters provide information on the stability of the coating under specific environmental conditions, while dynamic parameters reflect the performance of the coating under mechanical stress. This comprehensive evaluation method can more accurately predict and evaluate the comprehensive performance of the coating in practical applications.

[0041] Optionally, the weight coefficients of film thickness B, temperature T, salt spray concentration C, humidity D, scratch width E, scratch width after propagation F, and scratch width after peeling G are 0.15, 0.15, 0.2, 0.2, 0.1, 0.1, and 0.1, respectively.

[0042] First, the weight coefficients of salt spray concentration (C) and humidity (D) are designed to be 0.2. This is because salt spray concentration and humidity are key factors affecting the corrosion resistance of coatings. In actual application environments, high salt spray concentrations can cause rapid corrosion of metal substrates, especially in coastal or industrial areas, where the presence of salt spray can significantly accelerate the corrosion process on the metal surface. Similarly, high humidity can also aggravate this corrosion process because the presence of moisture promotes the occurrence of electrochemical corrosion. Therefore, higher weight coefficients are given to salt spray concentration and humidity to highlight their importance in evaluating coating durability.

[0043] Secondly, the weight coefficients of film thickness (B) and temperature (T) are both 0.15. Film thickness directly affects the protective performance of the coating. Thicker coatings usually provide better protection, but too thick coatings also lead to decreased flexibility and adhesion of the coating. Temperature affects the curing process and final performance of the coating. The appropriate temperature helps the coating achieve the best curing effect, thereby enhancing the adhesion and durability of the coating. Although these two parameters are important, their influence is relatively indirect compared to salt spray concentration and humidity, so their weights are slightly lower.

[0044] In addition, the weight coefficients of the scratch width (E), the scratch width after propagation (F), and the scratch width after peeling (G) are all 0.1. These parameters mainly reflect the reaction of the coating after mechanical damage, such as the initial damage level, the extension after damage, and the adhesion strength between the coating and the substrate. Although these parameters are very important for evaluating the mechanical properties of the coating, they are mainly problems that only appear after the coating is damaged. This means that under normal circumstances, these parameters have relatively little effect on the overall performance of the coating, so their weight in the comprehensive evaluation is low.

[0045] Through such a weight design, the present invention aims to balance the contribution of different parameters to the evaluation of coating adhesion, ensuring that the comprehensive evaluation takes into account both the impact of environmental factors on the coating and the performance of the coating under mechanical stress. This design makes the evaluation method more comprehensive and scientific, and can more accurately predict and evaluate the comprehensive performance of the coating under complex environmental and mechanical stress conditions. In general, this weight distribution method fully considers the importance of various factors in practical applications, thereby providing strong support for the comprehensive evaluation of coating performance.

[0046] Optionally, P i,min They represent the film thickness B of 25 μm, temperature T of -20°C, salt spray concentration C of 3 g / L, humidity D of 50%, scratch width E of 0.8 mm or 1.6 mm, scratch width F of 2 mm or 4 mm after propagation, and scratch width G of 3 mm or 6 mm after peeling.

[0047] P i,max They represent film thickness B 150μm, temperature T 40℃, salt spray concentration C 6g / L, humidity D 90%, scratch width E 1.2mm or 2.4mm, scratch width after propagation F 3mm or 6mm, and scratch width after peeling G 6mm or 12mm.

[0048] First, the minimum value of the film thickness B is set to 25μm and the maximum value is set to 150μm. This design ensures that the coating still has basic protection functions when it is thinnest, and provides the strongest protection when it is thickest. Secondly, the minimum value of the temperature T is set to minus 20℃ and the maximum value is set to 40℃. This design simulates different environmental conditions from extreme cold to high temperature. Low temperature can evaluate the stability and adhesion of the coating in a cold environment, while high temperature can test the performance of the coating under high temperature conditions to ensure that the coating can maintain good adhesion under various temperature conditions.

[0049] The minimum value of the salt spray concentration C is set to 3g / L, and the maximum value is set to 6g / L. This design can simulate the change from mild to severe corrosion environment. A lower salt spray concentration can evaluate the corrosion resistance of the coating under mild corrosion conditions, while a higher salt spray concentration can test the performance of the coating under severe corrosion conditions, ensuring the durability of the coating in different corrosion environments.

[0050] The minimum value of humidity D is set to 50% and the maximum value is set to 90%. This design covers different environmental conditions from medium humidity to extremely high humidity. Medium humidity can evaluate the performance of the coating under general humidity conditions, while extremely high humidity can test the performance of the coating in a humid environment to ensure the stability and adhesion of the coating under high humidity conditions. When the humidity D drops to less than 50%, such as 30%, the relevant formulas and weights no longer meet the requirements.

[0051] The minimum value of the scratch width E is set to 0.8mm or 1.6mm, and the maximum value is set to 1.2mm or 2.4mm. This design can evaluate the performance of the coating under different scratch widths. A smaller scratch width can evaluate the recovery ability of the coating under minor damage, while a larger scratch width can test the performance of the coating under severe damage.

[0052] The minimum width F of the scratch after propagation is set to 2mm or 4mm, and the maximum is set to 3mm or 6mm. This design can evaluate the performance of the coating under different damage extension conditions. A smaller propagation width indicates that the coating has better resistance to crack propagation, while a larger propagation width can test the performance of the coating under damage extension conditions.

[0053] The minimum value of the scratch peeling width G is set to 3mm or 6mm, and the maximum value is set to 6mm or 12mm. This design can evaluate the performance of the coating under different peeling conditions. A smaller peeling width indicates a stronger adhesion between the coating and the substrate, while a larger peeling width can test the performance of the coating under severe peeling conditions.

[0054] Through such a design, the present invention can not only comprehensively evaluate the stability of the coating under different environmental conditions, but also comprehensively evaluate the coating's recovery ability and durability from the perspective of mechanical damage. This comprehensive evaluation method helps to more accurately predict and evaluate the comprehensive performance of the coating in practical applications, thereby providing more references for the selection of coating materials, optimization of coating processes, and improvement of coating formulations, and continuously optimizing product design.

[0055] Optionally, the adhesion at the intersection of the horizontal and vertical parts of the cross-section is between 0.3 and 0.5 times the adhesion of a single line.

[0056] Setting the adhesion at the intersection of the horizontal and vertical grids to 0.3-0.5 times the single-line adhesion can more accurately reflect the true performance of the coating under complex stress conditions. In practical applications, coatings often experience higher stress concentration at intersections, which are usually the weakest points in coating adhesion. By setting the intersection adhesion to 0.3-0.5 times the single-line adhesion, the test results can be closer to the actual situation, thereby improving the accuracy and reliability of the test.

[0057] Secondly, this design helps to more comprehensively evaluate the comprehensive performance of the coating. In the cross-hatch test, single-line adhesion can evaluate the performance of the coating under straight scratches, while cross-point adhesion can test the performance of the coating under more complex stress conditions. By comparing single-line adhesion with cross-point adhesion, we can more comprehensively understand the performance of the coating under different stress conditions, thus providing a scientific basis for optimizing coating performance.

[0058] In addition, this design can improve the repeatability and comparability of test results. By setting a clear ratio range (0.3-0.5 times), the consistency of test results in different laboratories or batches can be ensured, which facilitates the comparison and verification of results under different conditions. This is of great significance for standardizing test methods and ensuring the reliability of test results. Setting the adhesion at the horizontal and vertical intersections of the grid to 0.3-0.5 times the single-line adhesion can not only more accurately reflect the true performance of the coating under complex stress conditions, but also improve the accuracy and reliability of the test results, providing strong support for the comprehensive evaluation of coating performance. This design helps to optimize the selection of coating materials and process improvements, thereby improving the overall performance of the product.

[0059] (III) Beneficial effects

[0060] The beneficial effects of the present invention are as follows: by introducing a quantitative evaluation method, the traditional method that relies on intuitive observation and empirical judgment is replaced, and the objectivity and reliability of the test results are significantly improved. Secondly, the test steps and conditions, such as coating thickness, specific parameters of salt spray and damp heat tests, are specified in detail to ensure the consistency and repeatability of the test process and facilitate the comparison of results between different laboratories. In addition, by defining the adhesion score A and setting a series of parameters and their weights, the quantitative evaluation of coating adhesion is achieved, providing clear data support for the improvement of coating performance. The present invention also clarifies the specific time arrangement of salt spray and damp heat tests (2 hours each time, at least 200 hours cumulatively), which helps to rationally plan the test cycle and improve test efficiency. Finally, by equally measuring the scratch width, width after propagation and width after peeling in the grid area, the precision of the coating adhesion evaluation is further improved.

[0061] In general, the present invention not only solves the subjectivity and uncertainty problems existing in traditional methods, but also provides a more scientific and systematic test and evaluation system, which helps to improve the quality control level of the surface coating of hydraulic supports. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] 1. Figure 1 Schematic diagram of the width of the scratch after propagation in Table 1 test scheme;

[0063] 2. Figure 2 Schematic diagram of the scratch width after propagation for the test scheme in Table 3. DETAILED DESCRIPTION

[0064] In order to better understand the above technical solution, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a clearer and more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.

[0065] Embodiment 1:

[0066] Use mechanical method to prepare scratches. The scratches should penetrate the waterborne polyurethane paint coating to the metal substrate. The scratches are parallel to the length and width of the sample. Each scratch has a fixed length and is divided into n equal parts. The width of the scratch is measured. The prepared scratched sample is tested in salt spray and damp heat environment. The time for each salt spray test and damp heat test is 2 hours, and these two tests are performed alternately until the cumulative time of the salt spray test and the cumulative time of the damp heat test reach 800 hours respectively. After the test, take it out for wet adhesion evaluation

[0067] After the test, take out the test sample and measure the width F of each scratch after propagation and the width G of the scratch after peeling. The evaluation should be carried out immediately and completed within 8 hours. This application uses a large amount of data collation and calculation, and the evaluation method is shown in Table 1, Table 2, Table 3 and Table 4. Use a 1mm sharp tool to peel off the coating from the scratch rust along the long side of the vertical scratch, and stop peeling to the coating firmly attached. When peeling to the coating firmly attached, the coating is damaged in a point-like manner and will not peel off in pieces, which means that the wet adhesion here has not yet begun to be lost.

[0068] Table 1. Summary of adhesion data under minimum test conditions.

[0069]

[0070] Table 2. Summary of adhesion data under the highest test conditions.

[0071]

[0072] Table 3. Summary of the third group of experiments

[0073]

[0074]

[0075] Table 4. Summary of the fourth group of experiments

[0076]

[0077] Group 1 (minimum test conditions)

[0078] See also Figure 1 , the first set of tests was conducted under the lowest test conditions, with the specific environmental parameters being: film thickness 25μm, temperature -20℃, salt spray concentration 3g / L, and humidity 50%. The test results showed that the adhesion score was between 0.8842 and 0.8972, with a final score of 0.893, and the coating fell off. This result shows that the coating adhesion is poor in an environment of extreme low temperature and low humidity. Low temperature (-20℃) causes the coating material to become brittle and hard, thereby reducing its flexibility and adhesion. In this case, the coating cannot be well bonded to the substrate and is prone to falling off in the cross-cut test, especially at the intersection. The film thickness is only 25μm, which is another influencing factor, because thinner coatings are not enough to provide an adequate protective layer, making it more likely to have problems in the cross-cut test.

[0079] Group 2 (highest test conditions)

[0080] The second set of tests was conducted under the highest test conditions, with specific environmental parameters: film thickness 150μm, temperature 40℃, salt spray concentration 6g / L, and humidity 90%. The test results showed that the adhesion score was between 0.8680 and 0.8970, with a final score of 0.882. Although the film thickness increased to 150μm, the combination of high temperature (40℃) and high humidity (90%) had a negative impact on the adhesion of the coating. High temperature can cause changes in the physical properties of the coating, such as softening or flow, which affects its bonding with the substrate. High humidity (90%) accelerates the process of water absorption and expansion of the coating, resulting in increased internal stress in the coating, which in turn affects its adhesion. In addition, high salt spray concentration (6g / L) will intensify the corrosion process, especially in high temperature and high humidity environments, where this corrosion effect is more obvious, making the coating more susceptible to erosion and peeling. Therefore, even if the film thickness increases, the adhesion of the coating under extreme high temperature and high humidity conditions is still poor.

[0081] Group 3 (moderate test conditions)

[0082] See also Figure 2 , the third group of tests was conducted under moderate test conditions, with the specific environmental parameters being: film thickness 100μm, temperature 25℃, salt spray concentration 5g / L, and humidity 60%. The test results showed that the adhesion score was between 0.9420 and 0.9606, with a final score of 0.952. Under these conditions, the coating exhibited very good adhesion. A moderate film thickness (100μm) can provide adequate protection without causing the coating performance to deteriorate due to excessive thickness. Both temperature (25℃) and humidity (60%) are ideal conditions, neither too harsh nor too loose, which are conducive to the curing and stability of the coating. A moderate salt spray concentration (5g / L) will not produce excessive corrosive effects on the coating. Therefore, under these moderate conditions, the coating can show a full state, the cutting edge is completely smooth, and there is no shedding phenomenon, showing good adhesion performance.

[0083] Group 4 (lower film thickness conditions)

[0084] The fourth group of tests was conducted under lower film thickness conditions, with specific environmental parameters of 50 μm film thickness, 35°C temperature, 4 g / L salt spray concentration, and 70% humidity. The test results showed that the adhesion score was between 0.9419 and 0.9508, with a final score of 0.946. Although the film thickness was only 50 μm, much lower than the 100 μm of the third group, the coating still showed high adhesion. This is because the temperature (35°C) and humidity (70%) are relatively mild conditions that will not have an excessively negative impact on the coating. Moderate salt spray concentrations (4 g / L) will not cause serious corrosion effects. Therefore, even with a thin film thickness, the coating can still maintain good adhesion under these conditions, showing that the coating material itself has good bonding properties.

[0085] In summary, the test results show that under extreme conditions (either low temperature and low humidity or high temperature and high humidity), the adhesion of the coating will be affected, while under moderate environmental conditions, the coating can show good adhesion even with a thin film thickness. These conclusions provide valuable reference information for the selection and optimization of the surface coating of hydraulic supports.

[0086] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may alter, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. A test of the cross-cutting adhesion of water-based paint for hydraulic supports, comprising the following steps: S1. Prepare the sample and spray the coating: Select the substrate and ensure that the surface is clean and free of impurities; Spray water-based paint to ensure that the coating thickness is between 25μm and 150μm; S2. Perform a cross-cut test: Use a 1mm or 2mm scratcher to draw a grid on the coating, make sure the scratches penetrate the coating to the substrate, and measure the width of the scratches; S3. Conduct salt spray and damp heat tests: Place the sample that has completed the cross-cut test in the test chamber and conduct salt spray and damp heat tests alternately. Each test is carried out according to the scheduled time. S4. Measure the width of the scratch after it spreads and the width of the scratch after it peels off in the cross-hatch area: Remove the specimen from the test chamber and observe and record the width of the scratch after propagation and the width of the scratch after peeling in the cross-cut area.

2. The cross-cut adhesion test according to claim 1, wherein in step S1, the water-based paint is a water-based polyurethane paint.

3. According to the cross-cut adhesion test of claim 1, in step S1, after spraying the water-based paint, the coating is allowed to dry naturally or baked to ensure that the coating is completely cured, the baking temperature is 80° C. to 100° C., and the baking time is 30 minutes to 1 hour.

4. The cross-hatch adhesion test according to claim 1, wherein in step S3, the duration of each salt spray test and damp heat test is 2 hours, and the two tests are performed alternately until the cumulative time of the salt spray test and the cumulative time of the damp heat test each reach at least 200 hours.

5. The cross-hatch adhesion test according to claim 1, wherein in steps S2 and S4, in each cross-hatch area, the length of the scratch is divided into a number of equal sections, and the scratch width, the scratch propagation width, and the scratch peeling width of each section are measured respectively.

6. A method for evaluating the cross-cut adhesion of water-based paint on hydraulic supports, characterized in that: The evaluation method is used to evaluate the cross-cut adhesion score of the water-based paint of the hydraulic support, and the calculated adhesion score A represents the magnitude of the cross-cut adhesion, thereby achieving a quantitative evaluation of the coating adhesion; In the formula, A j represents the adhesion score of the jth test point, A represents the average adhesion score of all test points; P i,j represents the measured value of the i-th parameter at the j-th detection point, P i,max represents the upper limit of the i-th parameter range, P i,min represents the lower limit of the i-th parameter range, n represents the number of measurement points, and w i Represents the weight of the i-th parameter.

7. The evaluation method according to claim 6, characterized in that: The evaluation method is to use a mechanical method to scratch the coating on the surface of the substrate to draw a plurality of quadrilaterals. i They represent film thickness B, temperature T, salt spray concentration C, humidity D, scratch width E, scratch width after propagation F and scratch width after peeling G respectively.

8. The evaluation method according to claim 7, characterized in that: The weight coefficients of film thickness B, temperature T, salt spray concentration C, humidity D, scratch width E, scratch width after propagation F, and scratch width after peeling G are 0.15, 0.15, 0.2, 0.2, 0.1, 0.1, and 0.1, respectively.

9. The evaluation method according to claim 7, characterized in that: P i,min They represent the film thickness B of 25 μm, temperature T of -20°C, salt spray concentration C of 3 g / L, humidity D of 50%, scratch width E of 0.8 mm or 1.6 mm, scratch width F of 2 mm or 4 mm after propagation, and scratch width G of 3 mm or 6 mm after peeling. P i,max They represent film thickness B 150μm, temperature T 40℃, salt spray concentration C 6g / L, humidity D 90%, scratch width E 1.2mm or 2.4mm, scratch width after propagation F 3mm or 6mm, and scratch width after peeling G 6mm or 12mm.

10. The evaluation method according to claim 7, characterized in that: The adhesion at the intersection of the horizontal and vertical lines of the crosshatch is between 0.3 and 0.5 times that of a single line.

Citation Information

Cited By

  • UV finish paint performance detection and analysis method and device based on image data processing

    CN119417824A

  • Coating corrosion resistance detection device suitable for large equipment

    CN120522064A